2011
DOI: 10.1179/102453311x12902908412110
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indices in diabetes mellitus: indicators of diabetic microvascular complications

Abstract: Platelet indices, especially PDW, are different between diabetics and controls as well as between diabetics with and without microvascular complications. Discriminant analysis using PDW and MPV could classify majority of patients with diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
125
4
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 11 publications
33
125
4
1
Order By: Relevance
“…The mean age of the diabetic population was 54.89 ± 10.201 years whereas that of nondiabetic population was 45. (2,3,4,6,9,10) Higher values of MPV were observed in our study among the diabetic subjects with microvasular complications such as Retinopathy and Microalbuminuria which was statistically significant. Higher values were also seen in studies done by Papanas et al and Ates et al (9,10) This suggested a role for the increased platelet activity in the pathogenesis of vascular complications.…”
Section: Resultssupporting
confidence: 50%
“…The mean age of the diabetic population was 54.89 ± 10.201 years whereas that of nondiabetic population was 45. (2,3,4,6,9,10) Higher values of MPV were observed in our study among the diabetic subjects with microvasular complications such as Retinopathy and Microalbuminuria which was statistically significant. Higher values were also seen in studies done by Papanas et al and Ates et al (9,10) This suggested a role for the increased platelet activity in the pathogenesis of vascular complications.…”
Section: Resultssupporting
confidence: 50%
“…20 Vagdatli et al 19 showed that PDW was a more specific marker for platelet activation. Jindal et al 21 showed that there is a significant increase in PDW levels for diabetic patients and the increase is more significant in patients with microvascular complications. In our study, we found that diabetic patients have higher PDW levels compared with the control group, but the differences were not reached to statistically significant level.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in hemostatic balance constitute a pathogenetic factor with a role in complication development in DM. Owing to the role of blood platelets in hemostatic balance, changes in platelets in diabetic patients have been studied extensively and an increase in thrombotic adhesion, aggregation and secretion has been shown in many of these [6][7][8].…”
Section: Discussionmentioning
confidence: 99%